Epidemiology of Genu Varum Patients In Dr. Soetomo General Academic Hospital Surabaya 2010-2018: A Retrospective Study - Hidayatullah, Ronaa Nuqtho; Martanto, Tri Wahyu ((JOINTS) Journal Orthopaedi and Traumatology Surabaya, 2022)
Background: Genu varum is a condition where the legs bend inward, resembling the letter "O," leading to gait disturbances and other lower-limb deformities. Data on genu varum, particularly regarding its prevention, is still lacking. This study aimed to identify the epidemiological characteristics of patients with genu varum to improve prevention, management, and prognosis, and to provide data for future research.Methods: This descriptive study employed a retrospective research design. Total sampling was used, including all genu varum patients from the Department of Orthopedics and Traumatology database at Dr. Soetomo General Academic Hospital Surabaya between 2010 and 2018. Data was collected from medical records and patient home visits.Results: Thirty-one patients were included in the study, with 21 males (68%) and 10 females (32%). The mean age of the patients was 4.3 years, with an average age at first complaint of 1.8 years. The average birth weight was 3.49 kg, and the average body mass index was 26.3. Langenskiold stage distribution was as follows: I (3%), II (70%), III (3%), IV (8%), V (3%), and VI (13%). Eighteen patients (58%) had bilateral Blount disease, seven (23%) had unilateral Blount disease, and six (20%) had physiological genu varum. Eighteen patients underwent conservative treatment, and 13 underwent operative treatment.Conclusion: Blount disease is the most common cause of genu varum at Dr. Soetomo General Academic Hospital, particularly in the infantile group. The majority of patients were male and received conservative treatment.